Graft octa-sulfonated poly(arylene ether) for high performance proton exchange membrane. Issue 24 (28th June 2015) - Feng, Sinan; Wang, Guibin; Zhang, Haibo; Pang, Jinhui
<x xml:space="preserve">Abstract</x> A novel octa-sulfonated poly(arylene ether) was combined with a longer hydrophobic backbone and grafted with ionic clusters, exhibiting high proton conductivity and excellent dimensional stability.